Management of orbital cellulitis and subperiosteal orbital abscess in pediatric patients: A ten-year review. (May 2017) - Sciarretta, Vittorio; Demattè, Marco; Farneti, Paolo; Fornaciari, Martina; Corsini, Ilaria; Piccin, Ottavio; Saggese, Domenico; Fernandez, Ignacio Javier
Abstract: Objective: Pediatric periorbital cellulitis represents a common disease complicating a nasal infection. Methods: A ten–year retrospective review of fifty-seven children admitted to our institution with the diagnosis of periorbital cellulitis as a complication of sinus infections was carried out. Results: The age varied from one month to eleven years (mean 3.9 years). Thirty-five were males (62%), while twenty-two were females (38%). Nine out of fifty-seven (15.8%) presented exophthalmos associated with eyelid erythema and edema, while the rest suffered mainly from eyelid erythema and edema. Twenty-two patients complaining of exophthalmos or not responding to medical therapy within 48 h were assessed with a computed tomography scan (38.6%). A subperiosteal orbital abscess was detected in nine cases and these patients underwent surgical drainage (15, 8%). Recurrence of orbital infection occurred in three cases (5.3%). Conclusions: Medical management is the main treatment for both preseptal and postseptal orbital cellulitis. Nevertheless, there is no universally accepted guideline for the treatment of subperiosteal abscesses and each case should be treated accordingly. Urgent surgical drainage should be considered in cases not responding to adequate medical management, or those cases presenting visual deterioration.